Board game as a medium for teaching and learning port management course - Mohd Radzi, Shanizan (2010)
This study aims to generate a board game prototype representing port activities. The study involved surveying activities taking place in the ports and developing a process flow model after each factors were identified. The process flow model that was developed was further transformed into board game method At the end of the study, a prototype board game with a port activity theme will be produced in hope to be utilized as alternative information medium for players to understand every process that happens in the port. The board game prototype is assured to correspond with the course syllabus of Port Management (PMG 3073) offered by Universiti Utara Malaysia as a non conventional learning method to help students in learning.